Economic Globalization, Income Inequality and Economic Growth in Nigeria: A Static Data Analysis (1986-2010) - Ogunyomi, Oluwatosin O.; Daisi, Olusegun Richard; Oluwashikemi, Rasaq Adebola (ABC Journal of Advanced Research, 2013)
This study examines the impact of economic globalization on income inequality and economic growth in Nigeria from 1986 to 2010. The study methodology was mainly Static Linear Econometric Model. Two models were used to test the two dependent variables simultaneously. The findings revealed that economic globalization had caused a widening income inequality as well as reduced economic growth of Nigerian economy due to much emphasis on financial globalization and other macroeconomic imbalances rather than trade globalization. It is therefore recommended that for Nigeria economy to exploit the gains of economic globalization just like the Asian Tigers, the Government should demonstrate good governance at all tiers of government through protectionist domestic policy, fiscal efficiency, political stability, adequate infrastructural provisions and encourages entrepreneurship development in Non-oil sectors to drastically reduce income equality between the unskilled and skilled labours.